2015
DOI: 10.22452/mjcs.vol28no3.5
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network-Based Speech Recognition Using Dwt Analysis Applied On Isolated Words From Oriental Languages

Abstract: Speech recognition is an emerging research area having its focus on human computer interactions (HCI 10,15, and 20 classes, 94.40%, and 91% accuracy ratefor 10,15, and 20 classes, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…According to previous works [22,23] and our experiments, embedding dimensiond=3 and time lag τ=1 are good choices to determine the RPS of speech signal. Fig.1 shows the RPSs of six speech signals with different emotions: anger, boredom, disgust, fear, joy, and sadness.…”
Section: ( 1)mentioning
confidence: 85%
See 1 more Smart Citation
“…According to previous works [22,23] and our experiments, embedding dimensiond=3 and time lag τ=1 are good choices to determine the RPS of speech signal. Fig.1 shows the RPSs of six speech signals with different emotions: anger, boredom, disgust, fear, joy, and sadness.…”
Section: ( 1)mentioning
confidence: 85%
“…Unfortunately, such a model cannot convey nonlinear 3D fluid dynamics phenomena of speech [20,21]. In order to fill the existing gap between this ideal linear deterministic model and real strongly unpredictable speech production process, non-linear processing techniques can be used [22,23,24,25].In recent years, reconstructed phase space (RPS) of speech has been used for speech recognition [26,27], speech enhancement [26,27]and detecting sleepiness [30]. Moreover, nonlinear dynamics features extracted from RPS of speech has been employed in SER.It has been shown that geometrical properties of RPScontain important emotional cues of speaker [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…There are different algorithms to train the neural network. The neural network has long been proven to be a good classifier and has been applied successfully in many complex and major classification problems [Bacha Rehmam et al (2015)] [M. Hariharan et al (2010)]. A feed forward neural network with one input layer with thirteen nodes, two hidden layers with thirteen nodes each and one output layer with three nodes is used here in our proposed method.…”
Section: Feed-forward Neural Networkmentioning
confidence: 99%
“…The hybrid between the two algorithms mean the position of particle updated, by applying a crossover operation, the data fly to a new search area if it swapped between two particles. So to avoid the local maxima we apply mutation to PSO to increase the diversity of the population [15,16]. Because of the mentioned disadvantages of GA and PSO, in this study, PSO hybrid with GA is proposed to improve the performance of each of those algorithms.…”
Section: Lbg-psoga Algorithmmentioning
confidence: 99%